STUDY OF THE ANCIENTY MORTARS IN THE CHURCH OF NOSSA SENHORA DA CONCEIÇÃO DA COMANDAROBA IN LARANJEIRAS SE/BR - da Silva, Eder Donizeti; Nogueira, Adriana Dantas; Alves, Daniel Ribeiro Chaves; Santos, Luís Marcondes Souza; Castro, Uallisson Vinicius Nascimento (Seven Editora, 2025)
In recent years, Conservation and Restoration Technology has faced, as usually happen in Sciences that are constantly changing and transforming, the need for adaptations in the face of new technologies, impositions and difficulties in the use of instruments and laboratory products/reagents for carrying out tests due to costs, health and environmental requirements, administrative policies, execution time, etc., and the natural scrupulous difficulty which has always existed in the non-destructive interventionist care that a heritage asset requires; these premises have imposed a reaffirmation/revaluation of knowledge in the face of rethinking the way in which one should act in studies involving the preservation of material cultural assets, in this case, specifically, in the collection of samples and laboratory tests. This paper follows the traditional methodology of analysis of mortars in historic buildings learned more than 20 years ago in the doctorate carried out in the postgraduate program in Architecture and Urbanism at the Federal University of Bahia and in post-doctorate carried out at the University of Lisbon/ National Laboratory of Civil Engineering (LNEC) in 2014 (financed by CAPES); these two experiences, related with numerous research works carried out at the CTPR (Center for Preservation and Restoration Technology) of the Federal University of Sergipe, led to the development of a technological initiation project (PIF11020-2022), between 2022 and 2023, with a view to the STUDY OF ANCIENT MORTARS FROM THE CHURCH OF NOSSA SENHORA DA CONCEIÇÃO DA COMANDAROBA IN LARANJEIRAS SE/BR, which revisits the traditional routines of historical mortar analysis, however, it proposes learning from the observation that precedes the choice and quantity of collection and a detailed critical reflective observation of these samples that allow the final choices for testing to fall on the qualitative assertion and represent effective scientific technical possibilities for the conservation/restoration of historical heritage buildings.DOI: https://doi.org/10.56238/sevened2025.029-005